Relation between temperature and wards humidity with air germs number in inpatient unit of RS PKU Muhammadiyah Jogjakarta - Ichtiarini Nurullita Santri; Dyah Suryani (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2015)
Background: The prevalence of nosocomial infections in Yogyakarta is quiet high, which is around 5,9%. Hospitalize patients are more prone to nosocomial infections. One of the non medical factor of nosocomial infections is environmental factor, such as temperatures and humidity, which enhance bacterial growth.Objective: The purpose of this study is to determine the correlation between temperature and wards humidity with air germs number in inpatients unit class I, II, and III of RS PKU Muhammadiyah Jogjakarta.Methods: This study was conducted as analitical study, in which laboratory tests and cross sectional approach was used. The sampling technique used was saturated sampling. The samples were 30 wards in inpatient unit of RS PKU Muhammadiyah Jogjakarta. VIP wards were excluded. Data were analyzed by chi-square test. Results: Bivariate analysis found that there is a significant correlation between temperature and wards humidity with air germs number in inpatients unit class I, II, and III of RS PKU Muhammadiyah Jogjakarta; with p=0.007, which is less than alpha (á=0.05), RP=2.25, CI=1.039-4.874 for temperature; and p=0.028, which is less than alpha (á=0.05), RP=1.968, CI=1.039-4.874 for humidity. Conclusion: There is a significant correlation between temperature and wards humidity with air germs number in inpatient units class I, II, and III of RS PKU Muhammadiyah Jogjakarta.